Agency, Security and Governance of Small States A Global Perspective - Kolnberger, Thomas; Koff, Harlan (Taylor & Francis, 2024)
Agency, Security and Governance of Small States examines what seems to be a deﬁning paradox of Small-State Studies: the simultaneous coexistence (and possible co-dependence) of vulnerability and opportunity related to small-state size. This book analyses small states within the framework of this apparent paradox. Traditionally, Small-State Studies has focused on three guiding questions: what constitutes a 'small state'? What explains small-state inﬂuence in global aﬀairs? Are small states truly vulnerable to security threats given the expansion of multilateralism and regionalism throughout the world? This book contends that new questions should be asked which recognise the important shifts in twenty-ﬁrst century security paradigms, to better understand how some states deploy their smallness as a resource for agency in supranational contexts. By varying historical, geographical, security, and governance contexts, the book embraces a most-diﬀerent-cases approach. The historical perspective is often neglected in Small-State Studies but contributes to understanding how small states have often, over time, transformed perceived insecurity into agency. By focusing on diﬀerent world regions, the authors enable the comparative analysis of collective actions, and the creation and implementation of institutions for 'common sense purposes' within a geographical region. Of particular contemporary importance, the book includes contributions which contend with hard-security issues alongside other soft-security challenges. The comparison of case studies conﬁrms that hard-security vulnerability and soft-security opportunities seem to be two sides of the same coin, which reinforces the book's focus on small-state paradoxes, and raises the question of whether smallness can be considered the deﬁning characteristic of governance in these countries. This book will have a broad appeal because of the diﬀerent world regions it analyses. It will be of interest to postgraduate students, scholars, and researchers of international relations, security, sustainability, governance, development, and political economy, as well as Small-State Studies.